2014
DOI: 10.1155/2014/307935
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Transportation Cost on Distribution-Free Newsboy Problems

Abstract: A distribution-free newsboy problem (DFNP) has been launched for a vendor to decide a product’s stock quantity in a single-period inventory system to sustain its least maximum-expected profits when combating fierce and diverse market circumstances. Nowadays, impacts of transportation cost on determination of optimal inventory quantity have become attentive, where its influence on the DFNP has not been fully investigated. By borrowing an economic theory from transportation disciplines, in this paper the DFNP is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Additionally, they provided an upper bound for the freight cost beyond which it becomes unprofitable to place any order with the supplier. Shu et al [18] studied the impacts of transportation cost on distribution-free newsvendor problems. They formulated the transportation cost as a nonlinear regression function of the shipping quantity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, they provided an upper bound for the freight cost beyond which it becomes unprofitable to place any order with the supplier. Shu et al [18] studied the impacts of transportation cost on distribution-free newsvendor problems. They formulated the transportation cost as a nonlinear regression function of the shipping quantity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They derived the closed-form formulas for the worst-case and best-case order quantities. Shu et al [17] considered the distribution-free single-period inventory management problem by borrowing an economic theory from transportation disciplines. Moon et al [18] found the differences between normal distribution approaches and distribution-free approaches in four scenarios with mean and variance.…”
Section: Introductionmentioning
confidence: 99%
“…Tajbakhsh [10] derived closedform expressions for the model of Moon and Choi [4]. Numerous models have been studied using the distributionfree approach [11][12][13][14][15][16]. For more details, one can refer to an extensive review of the literature provided by Qin et al [17].…”
Section: Introductionmentioning
confidence: 99%